The Ability of Training Approaches to Reduce Agricultural Knowledge Gaps between Men and Women in Rural Uganda - Tian Cai; Lulu Rodriguez; Eric Abbott (Journal of International Agricultural and Extension Education, 2014)
This study explores the effectiveness of three training methods (traditional lecture-field demonstration, lecture and field demonstration + video, and video only) to narrow the gap in knowledge about row bean planting between men and women farmers in Kamuli District,Uganda. Using a pretest-posttestquasi-experimental design, this study found that the method that combined video and lecture/demonstration was significantly more effective in narrowing the gender knowledge gap. Use of video alone improved women’s knowledge scores, but did not close the gap.
Keywords: training approaches; ICTs; gender knowledge gap; agricultural extension; row planting of beans; agricultural communication; rural livelihood